Exploring the Role of Social Media Platforms in Promoting Tourism Diversity - Suryana, Marceilla; Susanto, Eko; Prawira, Mega Fitriani Adiwarna; Afgani, Kurnia Fajar (Journal of Business Management Education (JBME), 2024)
This study explores the effectiveness of social media platforms for promoting various tourist attractions, including natural, man-made, and cultural tourism sites. By employing a descriptive research approach with a quantitative method, the study utilizes conjoint analysis with 100 respondents to gather insights. The findings reveal distinct tourist preferences regarding social media platforms for different attractions. Specifically, Instagram emerges as the most effective platform for promoting natural tourism, while Twitter shows less success. Conversely, YouTube is preferred for promoting cultural tourism, while Twitter is less effective. Twitter is perceived as relatively successful for man-made tourism, although not as effective as YouTube. These results highlight the importance of tailoring social media strategies based on the characteristics of each tourist attraction type rather than solely relying on platform popularity.